Identification of Dendritic Cell Maturation, TLR, and TREM1 Signaling Pathways in the Brucella canis Infected Canine Macrophage Cells, DH82, Through Transcriptomic Analysis - Park, Woo Bin; Kim, Suji; Shim, Soojin; Yoo, Han Sang (Frontiers in Veterinary Science, 2021)
Research has been undertaken to understand the host immune response to Brucella canis infection because of the importance of the disease in the public health field and the clinical field. However, the previous mechanisms governing this infection have not been elucidated. Therefore, in vitro models, which mimic the in vivo infection route using a canine epithelial cell line, D17, and a canine macrophage, DH82, were established to determine these mechanisms by performing an analysis of the transcriptomes in the cells. In this study, a coculture model was constructed by using the D17 cell line and DH82 cell line in a transwell plate. Also, a single cell line culture system using DH82 was performed. After the stimulation of the cells in the two different systems infected with B. canis, the gene expression in the macrophages of the two different systems was analyzed by using RNA-sequencing (RNA-seq), and a transcriptomic analysis was performed by using the Ingenuity Pathway Analysis (IPA). Gene expression patterns were analyzed in the DH82 cell line at 2, 12, and 24 h after the stimulation with B. canis. Changes in the upregulated or downregulated genes showing 2-fold or higher were identified at each time point by comparing with the non-stimulated group. Differentially expressed genes (DEGs) between the two culture models were identified by using the IPA program. Generally, the number of genes expressed in the single cell line culture was higher than the number of genes expressed in the coculture model for all-time points. The expression levels of those genes were higher in the single cell line culture (p < 0.05). This analysis indicated that the immune response-related pathways, especially, the dendritic cell maturation, Triggering receptor expression on myeloid cells 1 (TREM1) signaling, and Toll-like receptor (TLR) signaling pathway, were significantly induced in both the culture systems with higher p-values and z-scores. An increase in the expression level of genes related to the pathways was observed over time. All pathways are commonly associated with a manifestation of pro-inflammatory cytokines and early immune responses. However, the Peroxisome proliferator-activation receptor (PPAR) signaling and Liver X Receptor/Retinoid X Receptor (LXR/RXR) signaling associated with lipid metabolism were reduced. These results indicate that early immune responses might be highly activated in B. canis infection. Therefore, these results might suggest clues to reveal the early immune response of the canine to B. canis infection, particularly TLR signaling.